Reimaginasi Pendidikan Kebijakan Publik dan Hukum untuk Memperluas Ruang Sipil di Indonesia - Rizky Amalia Putri; Marlina; Dzaki Zain (Administratio, 2025)
Civil space in Indonesia is commonly understood through the lens of coercive restrictions, yet a less examined dimension is how education and the design of public participation shape young people’s access to policy processes. This study employs a sequential embedded design, combining document analysis of the regulatory framework for participation with an online survey of 567 Indonesian youth aged 16–30, selected through convenience sampling. The findings reveal three participatory capacity gaps: (1) the knowing–understanding gap—96.3% of respondents are familiar with the concept of policy participation, but only 43.7% understand its processes; (2) the understanding–doing gap—direct involvement is very low (19.2%); and (3) the access–influence gap—informational access does not translate into substantive influence. These patterns indicate that participatory exclusion is structural and reproduced through the disjunction between learning processes and regulatory design. This article contributes by offering an integrative framework for public policy–legal education that emphasizes procedural literacy and deliberative experience as strategies to expand a more inclusive civil space for youth.